Business intelligence: what we know so far, and what is ahead? - Talaoui, Yassine (My University, 2015)
The literature concerning business intelligence has grown rapidly during the last three decades; yet the knowledge about the interdependencies across Business intelligence (BI), competitive intelligence (CI), environmental scanning, and executive information system (EIS) remains far dispersed. This has resulted in a proliferation of fragmented literature duplicating identical endeavors. Although such pluralism expands our understanding of the idiosyncrasies of each concept, it fails to cumulate existing contributions to better address decision makers’ needs. Therefore, this article provides an integrative framework that outlines the covered research areas, and the underexplored ones. For this study, 35 keywords were applied to search evidence on the antecedents, mechanisms and outcomes of BI, CI, EIS, and environmental scanning. Based on the literature search of articles published in top-tier journals (ABS3 and ABS4 level) of accountacy, finance, information management, Innovation, general management, organization studies, strategic management, marketing, operations technology and management, operations research and management science, the present study identified 88 articles covering almost 30 years of scientific research (1985-2015) that focus on buiness intelligence. Building on previous literature, this paper identifies major patterns and contradictions across eight dimensions: 1) environmental antecedents; 2) organizational antecedents; 3) managerial and individual antecedents; 4) Business intelligence processes; 5) strategic outcomes; 6) tactical outcomes; 7) decision making; 8) organizational intelligence. By so doing, the developed framework sets the ground for scholars to further develop insights within each dimension. The framework presented, herein, provides guidance for both practitioners and scholars to probe further the spots crying for attention.
Keywords: Business intelligence; competitive intelligence; environmental scanning; executive information systems; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in Strategic Management|